GAMBARAN KEPATUHAN ORANG DENGAN HIV/AIDS (ODHIV) DALAM PENGOBATAN ANTIRETROVIRAL (ARV) DI INDONESIA - Sari, Puspita Rachma; Wahyuningsih, Sri (Jurnal Abdimas Bina Bangsa, 2024)
Human Immunodeficiency Virus (HIV) cases in Indonesia increase in 2023 according to information from the Ministry of Health of the Republic of Indonesia.1 Human Immunodeficiency Virus (HIV) is a virus that causes infection in leukocytes and can make the human immune system decrease. Meanwhile, Acquired Immunodeficiency Syndrome (AIDS) is the progression of the HIV infection stage. AIDS is a collection of several disease symptoms caused by the Human Immunodeficiency Virus (HIV). Antiretrovirals (ARVs) are drugs that can suppress the development of the HIV virus. The increase in HIV/AIDS cases also has an impact on the problem of adherence to taking antiretrovirals (ARVs) in People Living With HIV/AIDS (PLWHA). Adherence here means that PLWHA must take their medication with the right dose, the right rules of use and routinely take it every day on time. The necessity of PLWHA to take ARVs aims to suppress the number of viruses in the body. The rule of taking medication for life is a challenge for PLWHA. Adherence to antiretroviral treatment is the key to successful treatment in PLWHA. The purpose of this literature search is to find out the description of ODHIV compliance in various health care facilities both at Primary Health Care Facilities and Advanced Health Care Facilities and to find out what factors affect PLWHA adherence. A literature search was conducted on Google Scholar and Pubmed databases. Literature inclusion criteria were articles published in the last ten years, articles with interventions and articles without interventions that examined PLWHA adherence, factors affecting adherence. There where ten journal from the journal search and met the inclusion criteria